42.0k views
5 votes
What’s the answer to
5+3x=7(x+3)

1 Answer

5 votes

Answer:

-4

Explanation:

Simplifying

5 + 3x = 7(x + 3)

Reorder the terms:

5 + 3x = 7(3 + x)

5 + 3x = (3 * 7 + x * 7)

5 + 3x = (21 + 7x)

Solving

5 + 3x = 21 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.

5 + 3x + -7x = 21 + 7x + -7x

Combine like terms: 3x + -7x = -4x

5 + -4x = 21 + 7x + -7x

Combine like terms: 7x + -7x = 0

5 + -4x = 21 + 0

5 + -4x = 21

Add '-5' to each side of the equation.

5 + -5 + -4x = 21 + -5

Combine like terms: 5 + -5 = 0

0 + -4x = 21 + -5

-4x = 21 + -5

Combine like terms: 21 + -5 = 16

-4x = 16

Divide each side by '-4'.

x = -4

Simplifying

x = -4

User KaMZaTa
by
5.5k points